Social Convergence in Nordic NUTS-3 Regions - Marta Kuc (Institute of Economic Research (IER), 2017)
Geographical proximity, common historical roots and collaboration within the Nordic Council make the Nordic countries, often wrongly treated as monoliths. However, in reality, Nordic regions differ in terms of broadly defined social and economic development. Issues concerning the standard of living are one of the priorities of the Helsinki Treaty signed by Nordic countries. The main goal of this paper is to analyze the existence of the social convergence in the Nordic NUTS-3 regions over the 2000-2015 period. The social convergence refers to a reduction in the dispersion of the standard of living across regions. Result of this analysis may be helpful in evaluating the efficiency of the activities under third and fourth Nordic Strategy for Sustainable Development. The spatial taxonomy measure of development proposed by Pietrzak was used as the standard of living approximation. Inclusion of spatial relationships in the construction of taxonomic measure of development is justified as regions are not isolated in space and can be affected by other units. The existence of beta-, sigma- and gamma convergence was tested for global spatial aggregate measure and as well for sub-groups of determinants forming the standard of living. The analysis showed that the regions with the highest standard of living are those situated on the west coast of Norway. Regions with the lowest standard of living were regions located in central Finland. However the most important part of this research was to investigate the existence of beta-, sigma- and gamma- social convergence. The results show that there is no convergence for global standard of living measure. However the convergence occurs in groups of determinants of education and health care.
Keywords: C10; C43; I31; R12; 330; social convergence; Nordic regions; standard of living; taxonomy spatial measure of development